Competition between spin, charge, and bond waves in a Peierls-Hubbard model - Venegas, Pablo Antonio [UNESP]; Henríquez, Carlos; Rössler, Jaime (American Physical Society (APS), 1996)
We study a one-dimensional extended Peierls-Hubbard model coupled to intracell and intercell phonons for a half-filled band. The calculations are made using the Hartree-Fock and adiabatic approximations for arbitrary temperature. In addition to static spin, charge, and bond density waves, we predict intermediate phases that lack inversion symmetry, and phase transitions that reduce symmetry on increasing temperature.